Electrorheological properties of suspensions prepared from polythiophene conductive polymer - Chotpattananont D. (2014)
Electrorheological (ER) fluids are typically composed of polarizable particles dispersed in a non-conducting fluid. Upon the application of an electric field, chain-like or fibrillar aggregates of the suspended particles are oriented along the direction of the electric field, thereby inducing viscoelasticity and a drastic increase in viscosity. In our study, Poly(3-thiophene acetic acid), PTAA, has been developed for using as ER material. The rheological properties of this PTAA suspension upon the application of electric field were investigated under various deformations; oscillatory shear flow, steady shear, and creep. We found that PTAA based ER fluid exhibited viscoelastic behavior and showed the excellent responses under an applied electric field. Moreover, the ER response of this PTAA fluid was amplified with increases in electric field strength, particle concentration, and particle conductivity. Under the oscillatory shear, the dynamic moduli, G' and G", increased dramatically by 10 orders of magnitude, when the field strength was increased to 2 kV/mm. The suspensions exhibited a transition from fluid-like to solid-like behavior as the field strength increased. While under steady shear flow, the yield stress increased with electric field strength, E, and particle volume fraction, (φ, according to a scaling law of the form, τy Eoφ. Furthermore, the creep curves of this ER fluid consisted of both elastic and viscous responses and this fluid exhibits partially elastic recovery after the removal of applied stress. The creep properties strongly depended on the magnitude of an applied stress. Copyright © 2005 by ASME.